Networked Learning for Knowledge Mobilization: Universities and the Pursuit of Research Impact - MacGregor, Stephen; Phipps, David (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
Little is known about the university-based professionals who facilitate research impact and the networks they form to build institutional capacity. This article explores the efforts of Research Impact Canada, a pan-Canadian professional network dedicated to building institutional capacity for research impact across disciplines. Based on interviews with twenty key informants from the network, the analysis surfaced three overarching themes: a) the diversity of approaches to facilitating impact, b) the network’s ethos for networked learning, and c) key tensions inherent in networked learning. The findings suggest that dedicated institutional roles and units may contribute toward addressing the demands of facilitating impact, and that networked learning appears important in supporting these roles and units.